Towards magnetic resonance in scanning tunneling microscopy using heterodyne detection - Peter, Moritz (Experimental Condensed Matter Physics / Karlsruher Institut für Technologie, Physikalisches Institut, 2015)
The present work introduces a new concept for magnetic resonance measurements in the GHz regime inside a scanning tunneling microscope. It is based on heterodyne detection in a spin-polarized tunneling barrier. The experimental requirements, including a new method to suppress transmission effects, are explained. Measurements on three model systems which were studied to validate the new technique are presented and compared to simulations.